Prevalence of skin diseases and impact on quality of life in hilly region of Nepal - Shrestha, DP; Gurung, D; Rosdahl, I (Journal of Institute of Medicine Nepal, 2013)
The PDF of this article is available from http://jiom.com.np/index.php?journal=jiomjournal&page=article&op=view&path[]=580&path[]=537 Journal of Institute of Medicine, December, 2012; 34:44-49